Effects on Trade and the Economy from the Rapid Development of Technology in Indonesia - Arnold Robert Rondonuwu; Dwi Fitria Rahmadani; Ni Wayan Meika Suardiani; Fabya Gabriel Injilio Mokodompis; Nicola Miroslove Leonel Longdong (Publikasi Indonesia, 2026)
The rapid development of technology has significantly transformed trade dynamics and economic growth in Indonesia. However, the benefits of digital transformation remain unevenly distributed across regions, creating a digital divide that hinders inclusive development. This study aims to analyze the disparity between internet penetration and its economic utilization, as well as to identify barriers faced by non-connected populations in participating in the digital economy. A mixed-method approach was employed, combining quantitative descriptive analysis of secondary data from the Badan Pusat Statistik (BPS) and the Asosiasi Penyelenggara Jasa Internet Indonesia (APJII) (2025), with qualitative thematic analysis of policy documents and literature on digital inclusion. The findings reveal that although 80.67% of Indonesia's population are internet users, more than 55 million people remain unconnected, primarily in rural and remote areas. Furthermore, connectivity alone does not guarantee economic participation; limited digital literacy, inadequate infrastructure, low trust in digital financial services, and cultural barriers significantly impede the utilization of digital platforms for productive economic activities. The study also finds that existing policies tend to focus disproportionately on infrastructure expansion while neglecting capacity-building and community empowerment strategies. This research contributes to the formulation of more comprehensive digital development policies by emphasizing the necessity of integrating infrastructure investment with digital literacy programs, MSME empowerment, and social inclusion frameworks. The findings imply that bridging the digital divide requires a multidimensional approach that addresses not only access but also skills, trust, and institutional support to ensure sustainable and equitable digital transformation in Indonesia.